Estimating Efficiency in Domestic and Foreign Islamic Banking and Its Determinants among Three Neighboring Countries – Malaysia, Indonesia and Brunei - Loong, Foo Wei; Kamarudin, Fakarudin; Sufian, Fadzlan; M. Naseem, N. A. (School of Business and Economics, Universiti Putra Malaysia, 2017)
This study attempts to investigate the technical efficiency (TE)of domestic and foreign Islamic banks and its determinants for three neighborhood countries namely Malaysia, Indonesia and Brunei that spans over the period from 2006 to 2014.This study employs a two stage procedure involving data envelopment analysis (DEA) approach to measure banks’ efficiency while the parametric (t-test) and non-parametric (Mann-Whitney [Wilcoxon] and Kruskall-Wallis) to guage the difference in the efficiency between the domestic and foreign Islamic banks. Then, ordinary least squares (OLS) regressions is utilized to analyzed the determinants of technical efficiency. The results show that domestic Islamic bank for all countries exhibit significantly higher technical efficiency than foreign Islamic banks, which is consistent with home field advantage theory. The regressions on determinants results indicate that bank size and management quality have a negative and significant relationship with technical efficiency of Islamic banks, whereas market power and liquidity indicate a significantly positive relationship with technical efficiency of Islamic banks. The findings of this study give the banks’ stakeholders, regulators, banks’ managers and investors an important insight about the technical efficiency of Islamic banks and its significant determinants.